PROBIOTICS IN ORAL HEALTH – A REVIEW - RAMYA, D.; BABU, N. ARAVINDHA; MALATHI, L.; N, ANITHA; SANDHYAPRIYA, M (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Probiotics are supplements that contain beneficial yeasts or bacteria. They are provided in different quantities to promote effective colonization. These compounds support both the reduction of pathologic colonization and disease transmission as well as the activation of flora that promote wellness. According to definitions, probiotics are "live bacteria that, when given in sufficient quantities, confer a health benefit on the host." Among other therapies, antibiotics, immunosuppressive drugs, and radiation may change the makeup and affect the gut flora. Therefore, reestablishing microbial balance and averting disease may be made easier by introducing beneficial bacteria species into the gastrointestinal tract. Probiotic use in dentistry has become increasingly important as oral infections have become the most common type of infections in humans.